The Failure of Philosophical Knowledge Why Philosophers are not Entitled to their Beliefs - Tozsér, János (Bloomsbury Academic, 2023)
Philosophy begins and ends in disagreement. Philosophers disagree among themselves in innumerable ways, and this pervasive and permanent dissent is a sign of their inability to solve philosophical problems and present well-established substantive truths. This raises the question: "What should we do with our philosophical beliefs in light of philosophy's epistemic failure?" In this open access book, János Tozsér analyzes the possible answers to this question, develops them into comprehensive metaphilosophical visions, and argues that we cannot commit ourselves to any of them in peace, with a clear intellectual conscience, and without self-deception. Tozsér calls this disheartening insight "the experience of breakdown," claiming that no matter how we struggle, we are unable to create substantive philosophical knowledge that goes beyond the cost-benefit analysis of philosophical theories. He makes the case that, at the same time, we cannot suspend all of our beliefs about the most fundamental facts of our world once and for all, and so forever give up on seeking substantive philosophical truths. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Research Centre for the Humanities, Hungary.